Strain effects, potential profiles, and electronic properties of InAs/GaAs coupled double quantum dots with a disk shape - Kwon, Hye Young; Woo, Jun Taek; Lee, Dea Uk; Kim, Tae Whan; Park, Young Ju (WILEY-V C H VERLAG GMBH, 2009)
Strain potentials, potential profiles, and electronic subband energies of InAs/GaAs coupled double quantum dots (QDs) were calculated by using a finite-difference method (FDM) taking into account shape-based strain effects. The shape of the InAs/GaAs coupled double QDs on the basis of the transmission electron microscopy image was modeled to be a truncated hemi-ellipsoid. The interband transition energies from the ground electronic subband to the ground heavy hole band (E-1-HH1) in the InAs/GaAs coupled double QDs as determined from the FDM calcualtions taking into account strain effects, were in qualitatively reasonable agreement with the excitonic peaks corresponding to the (E-1-HH1) interband transistion eneries at several temperatures as determined from the temperature dependent photoluminescence spectra.